A SISTEM PEMESANAN PAKET TOUR AND TRAVEL PADA IKHLAS TRAVEL BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL: SISTEM PEMESANAN PAKET TOUR AND TRAVEL PADA IKHLAS TRAVEL BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL - Chindy Yovita Sukma; Yulia Agustina Dalimunthe; Al-Khowarizmi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
Ikhlas Travel is a travel agency based in Medan. Ikhlas Travel also has car rental services. At this time the existing system at Ikhlas Travel is still not in accordance with what is needed by prospective clients. This is because the ticket booking system is still done manually. Ikhlas Travel also provides car rental services where the system used in previous reservations is still via telephone, through personal to personal information and is still not computerized. With this Information System, it is very helpful in supporting the needs of prospective clients to get information in a relatively fast time. With that we need an information system that can provide information on ordering tickets and car rentals online based on a website, so that this information system can be easily accessed by prospective clients. Therefore, a website-based information system for Booking Tour and Travel Packages on Ikhlas Travel was created to make it easier for prospective clients to order. This website-based system was developed using the PHP programming language and the Laravel Framework. As for the system design method to be used is Rapid Application Development (RAD). Therefore, this computerized Tour and Travel Package Ordering System can be a solution that can be used on Ikhlas Travel to make it easier for prospective customers to order tour packages, so that later the system used can run efficiently and effectively.